Pengaruh Keterampilan Karyawan terhadap Kualitas Layanan di Salon Kecantikan Kota Padang Utara - Nadya Yasmin; Febri Silvia (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
This study aims to explore how employee skills contribute to the quality of service at beauty salons in North Padang. A quantitative method was used, with questionnaires distributed to 60 customers. The employee skills examined include basic abilities, technical know-how, interpersonal communication, and problem-solving. Service quality was assessed through five key indicators: reliability, responsiveness, assurance, empathy, and physical appearance. The findings reveal a clear connection between employee skills and the service quality experienced by customers. In short, the more capable the staff, the more satisfied the customers tend to be. This highlights the importance of skill development and continuous training for employees in the beauty service industry